Natural Course of Human T-Cell Leukemia Virus Type 1 Proviral DNA Levels in Carriers During Pregnancy. (16th January 2018) - Fuchi, Naoki; Miura, Kiyonori; Tsukiyama, Takashi; Sasaki, Daisuke; Ishihara, Kaori; Tsuruda, Kazuto; Hasegawa, Hiroo; Miura, Shoko; Yanagihara, Katsunori; Masuzaki, Hideaki
Abstract: The measurement of human T-cell leukemia virus type 1 (HTLV-1) proviral DNA levels by using polymerase chain reaction has been beneficial for confirming HTLV-1 infection during pregnancy. However, the influence of pregnancy on HTLV-1 infection and proviral DNA levels among pregnant women with HTLV-1 has not been clarified. We prospectively gathered blood samples from 36 pregnant women in whom HTLV-1 carriage was previously diagnosed and sequentially measured their proviral DNA levels. The HTLV-1 proviral DNA levels remained at a plateau during pregnancy but were elevated after delivery. Moreover, flow cytometry and serological analyses revealed that the regulatory T-cell population and soluble interleukin 2 receptor levels were similarly elevated after birth in comparison with those in control pregnant women. This study is the first to provide data on sequential changes in HTLV-1 proviral DNA levels during and after pregnancy. These findings will guide the establishment of a better program to prevent mother-to-child transmission of HTLV-1. Abstract : Human T-cell leukemia virus type 1 (HTLV-1) proviral DNA levels among pregnant women infected with HTLV-1 remained at a plateau during pregnancy but were elevated after delivery. This is the first report to provide data on the sequential changes in HTLV-1 proviral DNA levels during and after pregnancy.